The Effect of Humidity and Temperature on the Efficiency of Solar Power Panel Output in Dutsin-Ma Local Government Area (L.G.A), Nigeria - Baraya, Jamilu Tijjani; Abdullahi, Bello Hamza; Igwenagu, Ugochukwu Sylvester (Journal of Asian Scientific Research, 2019)
Solar energy is a large inexhaustible source of energy were the power from the sun intercepted by the Earth is over a trillion watt, which is many thousand times larger than the present consumption rate on the earth of all commercial energy sources. The sun could supply all the present and future energy need, presently the major way of extracting this energy is through solar panel and the efficiency of the energy conversion is in high consideration. Research has revealed that different factors can affect the efficiency of the panel, using a DT830B Digital Multi-meter and HTC-1 Clock/Temperature/Hygrometer on a Dp-Li21 polycrystalline solar panel. This work took the liberty of analyzing the effect of humidity and temperature on the efficiency of the solar panel. The result obtained shows that current production is highly aided by temperature within 42-45ºC and humidity below 35% and voltage production remains fairly stable with temperature below 42ºC and humidity below 60% while the power production is fairly stable with humidity below 40% and maximum with temperature at 45ºC, for power production on a panel mounted and to be mounted to be within maximum range, this analysis is to be carried out and put into consideration.